GWAS reveals genetic basis of a predisposition to severe COVID-19 through in silico modeling of the FYCO1 protein - Gusakova, Mariya S.; Ivanov, Mikhail V.; Kashtanova, Daria A.; Taraskina, Anastasiia N.; Erema, Veronika V.; Mikova, Valeriya M.; Loshkarev, Robert I.; Ignatyeva, Olga A.; Akinshina, Aleksandra I.; Mitrofanov, Sergey I.; Snigir, Ekaterina A.; Yudin, Vladimir S.; et al. (Frontiers in Medicine, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of COVID-19, is heavily reliant on its natural ability to "hack" the host's genetic and biological pathways. The genetic susceptibility of the host is a key factor underlying the severity of the disease. Polygenic risk scores are essential for risk assessment, risk stratification, and the prevention of adverse outcomes. In this study, we aimed to assess and analyze the genetic predisposition to severe COVID-19 in a large representative sample of the Russian population as well as to build a reliable but simple polygenic risk score model with a lower margin of error. Another important goal was to learn more about the pathogenesis of severe COVID-19. We examined the tertiary structure of the FYCO1 protein, the only gene with mutations in its coding region and discovered changes in the coiled-coil domain. Our findings suggest that FYCO1 may accelerate viral intracellular replication and excessive exocytosis and may contribute to an increased risk of severe COVID-19. We found significant associations between COVID-19 and LZTFL1, FYCO1, XCR1, CCR9, TMLHE-AS1, and SCYL2 at 3p21.31. Our findings further demonstrate the polymorphic nature of the severe COVID-19 phenotype.